Isolation and characterization of an Escherichia coli mutant lacking the cytochrome o terminal oxidase. - Au, D C (1985)
A respiration-deficient mutant of Escherichia coli has been isolated which is unable to grow aerobically on nonfermentable substrates such as succinate and lactate. Spectroscopic and immunological studies showed that this mutant lacks the cytochrome o terminal oxidase of the high aeration branch of the aerobic electron transport chain. This strain carries a mutation in a gene designated cyo which is cotransducible with the acrA locus. Mutations in cyo were obtained by mutagenizing a strain that was cyd and, thus, was lacking the cytochrome d terminal oxidase. Strain RG99, which carries both the cyd- and cyo- alleles, grows normally under anaerobic conditions in the presence of nitrate. Introduction of the cyd+ allele into the strain restores the respiration function of the strain, indicating that the cytochrome o branch of the respiratory chain is dispensable under normal laboratory growth conditions.